ЧИСЛЕННО-ПОЛЕВОЙ АНАЛИЗ АДЕКВАТНОСТИ ПРОЕКТНЫХ ДАННЫХ ТРЕХФАЗНЫХ АСИНХРОННЫХ ДВИГАТЕЛЕЙ И МЕТОД ИХ УТОЧНЕНИЯ НА ЭТОЙ ОСНОВЕ - Милых, В.И. (Інститут електродинаміки НАН України, Київ, 2018)
The principles and results of the numerically-field determination of the electromagnetic and energy parameters of the designed three-phase induction motors for the purpose of their verification analysis have presented. The analysis has realized with the magnetic field calculations in the FEMM software environment. Calculations have automated by the control program in the algorithmic language Lua. The data of a 15kW motor have used for the approbation of the method. The assessment of an adequacy of the motor designed parameters to its initial data has carried out on a magnetizing current, design tension and power. Studies have shown the problems of a motor designing by the classical method, where electromagnetic calculations have based on the magnetic circuit method. It has proposed to introduce a system of numerically-field calculations of the induction motor parameters as an efficacious basis for their refined design. References 17, tables 2, figures 3.